SINTESIS XANTON DARI ASAM 2-PHENOXYBENZOIC ACID SEBAGAI BAHAN DASAR OBAT MALARIA BARU - Amanatie Amanatie; Jumina Jumina; Mustofa Mustofa; M. Hanafi (Jurnal Kimia Terapan Indonesia, 2013)
Synthesis of xanthone was conducted from the raw material of 2-phenoxybenzoic acid through acid-catalyzed-cyclization. The product was characterized using UV- Vis, 1 13 d FT-IR, H-NMR, C-NMR, an LC-MS Cyclization of 2-phenoxybenzoic acid using sulfuric acid catalyt gave xanthone in 86.11 % yield. These compounds as the basis of new malaria drugs.Keywords 2-phenoxybenzoic acid, Synthesis, Xanthone, Characterized.